Development of an intelligent IoT-Based Monitoring System for Power Quality Application - Nazree, Muhammad Farid bin Nazree; Hong Yin, Lam (Progress in Engineering Application and Technology, 2022)
A process on solar charging system where there is a solar panel, battery and the load as for charging the battery the solar charger is needed to complete the system. The problem that is occur is providing sustainability of energy and to relieving the global environmental crisis. Th power production is need for accurate solar power forecasting its crucial for grid integration when its directly connected with their accuracy. As for data loggers for PV monitoring there are some research regarding the best way to collect the data needed. As the precise and simplest way is using the data logger. There are several researches proposed that the data logger is necessary for monitoring and collecting data. The requirement also has been measured which there are several instinct levels that can reach the main goal of measurements. As for the performance and testing of its results within the accurate range, the multimeter is the base guideline to validate our measurements in this project. This standard can be defined as class B (medium accuracy) as the most ideal system and fit for our application. Among all the various connectivity fir out online monitoring system, there are several of frequency we need to address, on of it the connection to the internet and it is reliable of connection without any networking problem. There are several characteristic the best is WLAN(Wi-Fi) which suitable and fast if the bandwith application. In this project, we build a prototype which can monitor the solar panel to gain data and collect all measurements needed. PV system, monitoring is regarded as a critical feature for assessing the system's stability and performance. For collecting data with simple GUI interface that has been create. The cloud data is been store in the firebase online, which is being link to the GUI system app. Without losing any data, the system will continue collect if there any problem in the online system. As it restores all the necessary data. The real time monitoring system is been accomplish as the main objective is been achieve as for the precision of 100% as the manual data collecting.